Competency-Based Learning in Maritime Vocational Higher Education: A Systematic Literature Review - Nur Rohmah (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
Maritime vocational higher education plays a strategic role in preparing human resources capable of meeting the needs of the ever-growing and increasingly competitive maritime sector. The dynamics of the maritime industry, characterized by technological developments, increasingly stringent work standards, and the need for a ready-to-work workforce, demand learning that is oriented towards achieving students' true capabilities. However, in practice, there is still a gap between the learning process in maritime vocational higher education and the real needs of the workplace, both in terms of learning orientation, the role of educators, and integration with industry. This study aims to examine in depth the implementation of competency-based learning in maritime vocational higher education and its commitment to graduate readiness and competitiveness. This study uses a qualitative approach through the review and analysis of various literature sources and previous research results relevant to competency-based learning and maritime vocational education. The results indicate that the direction and orientation of learning that align with the needs of the maritime industry play a crucial role in shaping graduates' work readiness. The role of educators, practical instructors, and an integrated learning environment also supports the achievement of students' professional skills and attitudes. Furthermore, integrating learning with the needs of the maritime industry, despite facing various challenges, opens up opportunities for continuous learning innovation to improve the quality and competitiveness of maritime vocational higher education graduates.